The Enigmatic Roles of PPR‐SMR Proteins in Plants. Issue 13 (6th May 2019) - Zhang, Yi; Lu, Congming
Abstract: The pentatricopeptide repeat (PPR) protein family, with more than 400 members, is one of the largest and most diverse protein families in land plants. A small subset of PPR proteins contain a C‐terminal small MutS‐related (SMR) domain. Although there are relatively few PPR‐SMR proteins, they play essential roles in embryo development, chloroplast biogenesis and gene expression, and plastid‐to‐nucleus retrograde signaling. Here, recent advances in understanding the roles of PPR‐SMR proteins and the SMR domain based on a combination of genetic, biochemical, and physiological analyses are described. In addition, the potential of the PPR‐SMR protein SOT1 to serve as a tool for RNA manipulation is highlighted. Abstract : Pentatricopeptide repeat‐small MutS‐related (PPR‐SMR) proteins play essential roles in embryo development, chloroplast biogenesis and gene expression, and retrograde signaling. The PPR motifs and SMR domain of the PPR‐SMR protein SOT1 confer RNA sequence specificity and endonucleolytic activity, respectively. SOT1 could be used as a tool for RNA manipulation, particularly in studies of chloroplast and mitochondrial biology and RNA viral defense.